Demarcating the membrane damage for the extraction of functional mitochondria. (December 2018) - Rahman, Md; Xiao, Qinru; Zhao, Shirui; Qu, Fuyang; Chang, Chen; Wei, An-Chi; Ho, Yi-Ping
Abstract Defective mitochondria have been linked to several critical human diseases such as neurodegenerative disorders, cancers and cardiovascular disease. However, the detailed characterization of mitochondria has remained relatively unexplored, largely due to the lack of effective extraction methods that may sufficiently retain the functionality of mitochondria, particularly when limited amount of sample is considered. In this study, we explore the possibility of modulating hydrodynamic stress through a cross-junction geometry at microscale to selectively disrupt the cellular membrane while mitochondrial membrane is secured. The operational conditions are empirically optimized to effectively shred the cell membranes while keeping mitochondria intact for the model mammalian cell lines, namely human embryonic kidney cells, mouse muscle cells and neuroblastoma cells. Unsurprisingly, the disruption of cell membranes with higher elastic moduli (neuroblastoma) requires elevated stress. This study also presents a comparative analysis of total protein yield and concentrations of extracted functional mitochondria with two commercially available mitochondria extraction approaches, the Dounce Homogenizer and the Qproteome® Mitochondria Isolation Kit, in a range of cell concentrations. Our findings show that the proposed "microscale cell shredder" yields at least 40% more functional mitochondria than the two other approaches and is able to preserve the morphological integrity of extracted mitochondria, particularly at low cell concentrations (5–20 × 104 cells/mL). Characterized by its capability of rapidly processing a limited quantity of samples (200 μL), demarcating the membrane damage through the proposed microscale cell shredder represents a novel strategy to extract subcellular organelles from clinical samples. Microfluidics: extracting mitochondria A microfluidic device enables the shearing of cell membranes without causing substantial damage to mitochondria. Understanding the mechanisms of mitochondria is facilitated by isolating them from their host cell, so that they can be studied without influence from other organelles. Shearing the cell membrane to release the mitochondria is a common approach, but can also result in damage to the mitochondria. Now, a team led by Yi Ping Ho from The Chinese University of Hong Kong reports a "microscale cell shredder" based on a cross-junction microchannel device, in which the cell suspension and buffer are introduced into opposite ends, with the resulting stretch of cell membrane, releasing the mitochondria. The "microscale cell shredder" achieves a 40% increase in extracted functional mitochondria, as compared to existing approaches.